Identifying Risk and its Impact on Contracting Through a Benefit Based-Model Framework in Business to Business contracting: Case of the defence industry - Ng, I.; Yip, N. (Cranfield University Press, 2009)
Two defence contracts for availability are studied in the attempt to better understanding the provision of service in a maintenance, repair and overhaul environment that is contracted on the performance of the equipment, rather than merely providing equipment. The nature of the contract changes the dynamics of the delivery, bringing behavioural issues into the forefront, with both customer and firm focused on value cocreation, rather than each party’s contractual obligation. Our study provides a customer focused approach that exposes gaps in the way organizations approach their service provision in MRO. We argue that customer involvement and behavioural issues in the co-creation process has to be factored into the design and delivery of traditional MRO delivery systems. This paper uncovers four areas that pose risks to performance based contracts and are crucial in the design of services under such a contractual environment and provides a research agenda for future studies in this area.
Organised by: Cranfield University
Keywords: Co-Creation; Performance Based-Contracts; Risks; Contract Design